Cross-platform UI development with Xamarin. Forms : create fully operational applications and deploy them to major mobile platforms using Xamarin. Forms /: create fully operational applications and deploy them to major mobile platforms using Xamarin. Forms. (2015) - Johnson, Paul F
No abstract available